THE ROLE OF WORKPLACE FRIENDSHIP NETWORKS IN FOSTERING EMPLOYEE CREATIVITY - Battulga, Altantsetseg; Erdene-Ochir, Bilegt (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
As a result, there is growing interest in understanding the factors that influence creativity. While previous studies have extensively examined both employee creativity and workplace friendships, few have explored the connection between the two. This study investigates how the structure of workplace friendship networks, the breadth of social circles, and the nature of interpersonal relationships influence employee creativity. The research surveyed 129 employees from an independent unit of a state-owned enterprise, quantitatively assessing the number of friends, the number of friendship groups, and individual creativity levels. The findings reveal that both the number of friendship groups and close interpersonal connections positively impact employee creativity. These results underscore the importance of trust-based social networks in cultivating a creative organizational environment. The study concludes by discussing its theoretical and practical implications and outlining directions for future research.